(untitled) (Swiss Medical Weekly, 2012)
Roflumilast is a selective phosphodiesterase 4 inhibitor which has been licensed in the European Union since 2010 and in Switzerland since November 2011 as an add-on treatment for patients with chronic obstructive pulmonary disease (COPD) in GOLD (Global Initiative for Chronic Obstructive Lung Disease) stages 3 and 4 (FEV1 <50% predicted after bronchodilatation) and frequent exacerbations despite correctly-dosed therapy with a long-acting bronchodilator. Roflumilast is designed to target both the systemic and pulmonary inflammation associated with COPD. In this review roflumilast’s chemistry, pharmacodynamics, pharmacokinetics, clinical efficacy, safety and tolerability and the current ongoing clinical trials involving roflumilast are outlined. Information has been sourced from the Swiss and US product information monographs, peer-reviewed published literature (identified from a PubMed MEDLINE search 1966 – March 2012 using the term “roflumilast”), the COPD GOLD international guidelines for the management of COPD (Revised 2011) and an independent analysis of phase 3 clinical trial data by FDA staff physicians. Clinical efficacy in terms of a modest gain in FEV1% and a reduction in exacerbation rate has been demonstrated in phase 3 clinical trials and roflumilast has been recently incorporated into international treatment guidelines. However data examining roflumilast as add-on therapy to long-acting bronchodilators and ICS (standard therapy) is currently awaited and phase 4 post-marketing studies are required to determine the incidence and severity of adverse events and the long-term beneficial effects of roflumilast as a maintenance therapy for COPD in every-day clinical practice.